Severe lower limb malformation associated with other deformities and death in infancy in two brothers. Issue 5 (October 1977) - Fried, K; Goldberg, M D; Mundel, G; Reif, R
Abstract : Two brothers with severe and rare lower limb malformations but normal upper limbs are described. Both brothers had glans hypospadias and they died in early infancy. In the first brother the limb malformation was a severe deformity of the right foot which was split and of rockerbottom shape with oligosyndactyly. In the second brother the right limb below the knee was more severely deformed while only the toes were involved in the left limb. Details of the clinical and pathological findings are described. The most likely mode of inheritance of this rare syndrome is autosomal recessive or X-linked recessive with variable expressivity.